A Fluorescent "Allosteric Scorpionand" Complex Visualizes a Biological Recognition Event. Issue 2 (9th January 2013) - Yu, Mingfeng; Yu, Qun; Rutledge, Peter J.; Todd, Matthew H.
Abstract We describe a new class of fluorescent reporter and its employment to visualize the biotin/avidin binding interaction. Derivatives of the azamacrocycle cyclam that contain a pendant naphthalimide dye are inherently fluorescent when zinc(II) is coordinated. Introducing a second pendant group—biotin—affords an unsymmetrical bis‐triazole‐scorpionand ligand that interacts specifically with avidin. This ligand has been assembled by using a one‐pot "double‐click" strategy and complexed with copper(II) and zinc(II). The zinc(II) complex is fluorescent, and its fluorescence output changes in the presence of avidin. Upon avidin binding, the fluorescence output is diminished by interaction with the protein, at [complex]/[avidin] ratios of up to 4:1. The observed change might arise from a specific quenching effect in the biotin binding pocket or from a binding‐induced change in the coordination geometry of the complex.